Evolution of the Dynamics of Centennial Hot Summers in Western Europe With Climate Change - Robin Noyelle; Arnaud Caubel; Yann Meurdesoif; Davide Faranda; Pascal Yiou (Geophysical Research Letters, 2025)
Abstract The intensity and frequency of heat extremes is expected to increase with climate change. However, answering questions about their physical mechanisms and how they may evolve in the future is challenging because of their rareness. Here we investigate the evolution of the mechanisms leading to heat extremes in Western Europe with climate change. We use a rare event algorithm to increase the number of extremely hot summers in Western Europe simulated in the IPSL‐CM6A‐LR climate model under present, SSP2‐4.5 and SSP3‐7.0 forcings. We show that centennial hot summers arise because of a succession of heatwaves, occurring through the local amplification of a synoptic scale Rossby wave packet and the advection of sensible heat from eastward regions. The atmospheric dynamics of these summers become more local in the future, and more driven by regional diabatic heat fluxes than by the large scale organization of the atmosphere.